Hyponatremia and its associated factors in children admitted to the pediatric intensive care unit in eastern Ethiopia: a cross-sectional study - Yeshi Berhanu; Turina Yusuf; Ahmed Mohammed; Fentahun Meseret; Betelhem Demeke Habteyohans; Ayichew Alemu; Gadissa Tolosa; Mulualem Keneni; Fitsum Weldegebreal; Assefa Desalew (BMC, 2023)
Abstract Background Hyponatremia is a serious problem that leads to substantial increases morbidity and mortality in critically ill children. The identification of risk factors, implementation of preventive measures, and timely diagnosis and management are crucial to reduce adverse events related to hyponatremia. Despite the higher burden of the problem in Ethiopia, evidence related to the risk factors for hyponatremia among children in Ethiopia is limited; in particular, no study has been identified in eastern Ethiopia. Therefore, we aimed to determine the magnitude of hyponatremia and its associated factors in children admitted to the pediatric intensive care unit at the Hiwot Fana Comprehensive Specialized University Hospital. Methods A facility-based cross-sectional study was conducted using 422 medical records of pediatric patients admitted to the pediatric intensive care unit at Hiwot Fana Comprehensive Specialized University Hospital from January 2019 to December 2022. Medical records were reviewed to collect data. Data were analyzed using a statistical package for social sciences (SPSS) version 26. A binary logistic regression model with an adjusted odds ratio (aOR) and a 95% confidence interval (CI) was used to identify factors associated with the outcome variable. Statistical significance was set at p < 0.05. Results The magnitude of hyponatremia was 39.1% (95% CL: 34.4-43.8%). The age of the child (aOR = 2.37;95% CL:1.31-4.31), diagnosis of sepsis (aOR = 2.33; 95% CL:1.41-3.84),   surgical procedures (aOR = 2.39; 95% CL:1.26-4.56), nutritional status (aOR = 2.60; 95% CL:1.51-4.49), and length of hospital stay (aOR = 3.04; 95% CL: 1.73-5.33) were factors significantly associated with hyponatremia. Conclusions Four out of ten children admitted to pediatric intensive care units had hyponatremia. Hyponatremia was significantly associated with the age of the child, malnutrition, sepsis, surgical procedures, and length of hospital stay. To reduce the burden of hyponatremia and associated mortality, attention should be focused on improving the care of malnourished children, and those with sepsis, and the quality of postoperative monitoring services. Moreover, intervention strategies aimed at reducing the burden of hyponatremia should target the identified factors.